Estimation of Aerodynamic Coefficients in a Small Subsonic Wind Tunnel - Krajček Nikolić, Karolina; Domitrović, Anita; Janković, Slobodan (Promet - Traffic&Transportation, 2018)
To apply the experimental data measured in a wind tunnel for a scaled aircraft to a free-flying model, conditions of dynamical similarity must be met or scaling procedures introduced. The scaling methods should correct the wind tunnel data regarding model support, wall interference, and lower Reynolds number. To include the necessary corrections, the current scaling techniques use computational fluid dynamics (CFD) in combination with measurements in cryogenic wind tunnels. There are a few methods that enable preliminary calculations of typical corrections considering specific measurement conditions and volume limitation of test section. The purpose of this paper is to present one possible approach to estimating corrections due to sting interference and difference in Reynolds number between the real airplane in cruise regime and its 1:100 model in the small wind tunnel AT-1. The analysis gives results for correction of axial and normal force coefficients. The results of this analysis indicate that the Reynolds number effects and the problem of installation of internal force balance are quite large. Therefore, the wind tunnel AT-1 has limited usage for aerodynamic coefficient determination of transport airplanes, like Dash 8 Q400 analyzed in this paper.